The Memory of Emotions in View of Linguistics (Based on the Reminiscent Narratives from the Archive of Oral History of the Warsaw Uprising) - Duda, Beata; Ficek, Ewa (2024)
The article presents a research project devoted to the linguistic/discursive description of the affective dimension of oral history narratives, and more precisely – reminiscent accounts of history witnesses from the Archive of Oral History of the Warsaw Uprising. The authors of the text demonstrate: 1. the reasons for interest in the topic; 2. the subject and purpose of the inquiry; 3. the inquiry’s theoretical and methodological background – mainly memory linguistics and corpus-aided discourse analysis (CADS); 4. the source material; 5. the conclusions from the exemplary analytical procedure related to the project; 6. the cognitive, application and pro-social value of the project, including new/important aspects of the results that can be obtained thanks to the project compared to the results obtained by other authors. Detailed research (quantitative and qualitative research) of lexical updates of reflective emotions referring to the past and present in authentic statements of the Warsaw Uprising participants (active and passive ones), as well as of the emotional overtones of the insurgents’ statements will allow to determine the role of affective phenomena in shaping the image(s) of this event in collective memory/memory discourses. The research will also contribute to the recognition of the emotional history of the events of 1944.
Keywords: Warsaw uprising; emotional memories; reflective emotions; memory linguistics; corpus-assisted discourse analysis